The impact of postoperative aspirin in patients undergoing Woven EndoBridge: a multicenter, institutional, propensity score-matched analysis - Dmytriw, Adam A.; Musmar, Basel; Salim, Hamza; Aslan, Assala; Cancelliere, Nicole M.; McLellan, Rachel M.; Algin, Oktay; Ghozy, Sherief; Dibas, Mahmoud; Lay, Sovann V.; Guenego, Adrien; Renieri, Leonardo; et al. (Journal of neuroInterventional surgery, 2025)
Background The Woven EndoBridge (WEB) device is frequently used for the treatment of intracranial aneurysms. Postoperative management, including the use of aspirin, varies among clinicians and institutions, but its impact on the outcomes of the WEB has not been thoroughly investigated. - Methods This was a retrospective, multicenter study involving 30 academic institutions in North America, South America, and Europe. Data from 1492 patients treated with the WEB device were included. Patients were categorized into two groups based on their postoperative use of aspirin (aspirin group: n=1124, non-aspirin group: n=368). Data points included patient demographics, aneurysm characteristics, procedural details, complications, and angiographic and functional outcomes. Propensity score matching (PSM) was applied to balance variables between the two groups. - Results Prior to PSM, the aspirin group exhibited significantly higher rates of modified Rankin scale (mRS) mRS 0-1 and mRS 0-2 (89.8% vs 73.4% and 94.1% vs 79.8%, p<0.001), lower rates of mortality (1.6% vs 8.6%, p<0.001), and higher major compaction rates (13.4% vs 7%, p<0.001). Post-PSM, the aspirin group showed significantly higher rates of retreatment (p=0.026) and major compaction (p=0.037) while maintaining its higher rates of good functional outcomes and lower mortality rates. In the multivariable regression, aspirin was associated with higher rates of mRS 0-1 (OR 2.166; 95% CI 1.16 to 4, p=0.016) and mRS 0-2 (OR 2.817; 95% CI 1.36 to 5.88, p=0.005) and lower rates of mortality (OR 0.228; 95% CI 0.06 to 0.83, p=0.025). However, it was associated with higher rates of retreatment (OR 2.471; 95% CI 1.11 to 5.51, p=0.027). - Conclusions Aspirin use post-WEB treatment may lead to better functional outcomes and lower mortality but with higher retreatment rates. These insights are crucial for postoperative management after WEB procedures, but further studies are necessary for validation.
Gesehen am 21.02.2025
Published online first: 18 January 2024